2018
DOI: 10.1186/s12891-018-2008-8
|View full text |Cite
|
Sign up to set email alerts
|

Change in muscle volume after steroid therapy in patients with myositis assessed using cross-sectional computed tomography

Abstract: BackgroundSteroid therapy, a key therapy for inflammatory, allergic, and immunological disorders, is often associated with steroid myopathy as one of the side effects. Steroid therapy is considered the first-line therapy for myositis; however, there have been no reports strictly comparing the muscle mass in patients with myositis before and after steroid therapy. Thus, it is currently unclear whether steroid therapy for such patients affects muscle volume in addition to muscle strength. We aimed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…To the contrary, patients performed on average better after 3 and 6 months, except for the number of chair stands that decreased gradually at follow‐up visits. Nawata et al also reported an improvement in muscle strength after 3 months of glucocorticoid treatment despite a significant reduction in muscle volume.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…To the contrary, patients performed on average better after 3 and 6 months, except for the number of chair stands that decreased gradually at follow‐up visits. Nawata et al also reported an improvement in muscle strength after 3 months of glucocorticoid treatment despite a significant reduction in muscle volume.…”
Section: Discussionmentioning
confidence: 95%
“…A recent case study of Cushing's syndrome myopathy suggested the usefulness of muscle echo intensity as a recovery sign after resolution of the hypercortisolemic state . Moreover, Nawata et al recently used computed tomography and showed a significant reduction in muscle mass ( P = .039) in a mixed group of patients taking glucocorticoids (>30 mg/d) for an average of 3 months. However, the usefulness of computed tomography is complicated by the cost and exposure to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations